IDENTIFICATION OF DIFFERENTIALLY EXPRESSED ABIOTIC STRESS-INDUCED GENES IN TEFF GRASS (E RAGROSTIS TEF) LEAVES - Ki-Won Lee; Md. Atikur Rahman; Gi Jun Choi; Hee Chung Ji; Tae Young Hwang; Sang-Hoon Lee (Journal of Animal and Plant Sciences, 2018)
The responses of plants to salinity and heavy metals have been extensively studied; however, the relevant stress- responsive genes in teff grass have not previously been investigated. Here, we identified differentially expressed genes (DEGs) in teff grass (Eragrostis tef cv. Tiffany) leaves under conditions of salt and arsenic stress, by using an annealing control primer (ACP)-based differential display reverse transcriptase-PCR method with 120 arbitrary ACPs. We observed the up-regulation of 6 DEGs, including 2 newly induced DEGs. Under conditions of arsenic stress, the 2 newly induced DEGs were identified as Bax inhibitor 1. We propose that the newly induced and up-regulated genes play a central role in plant detoxification metabolisms against salt and arsenic. In addition, these genes may enhance the phytotoxic response of teff grass. development of crop plants with enhanced tolerance to
Keywords: Arsenic; DEGs; Salt stress; Teff grass.